Sustained Malaria Control Over an 8-Year Period in Papua New Guinea: The Challenge of Low-Density Asymptomatic Plasmodium Infections - Koepfli, Cristian (J Infect Dis, 2017)
BACKGROUND: The scale-up of effective malaria control in the last decade has resulted in a substantial decline in the incidence of clinical malaria in many countries. The effects on the proportions of asymptomatic and submicroscopic infections and on transmission potential are yet poorly understood. METHODS: In Papua New Guinea, vector control has been intensified since 2008, and improved diagnosis and treatment was introduced in 2012. Cross-sectional surveys were conducted in Madang Province in 2006 (with 1280 survey participants), 2010 (with 2117 participants), and 2014 (with 2516 participants). Infections were quantified by highly sensitive quantitative polymerase chain reaction (PCR) analysis, and gametocytes were quantified by reverse-transcription qPCR analysis. RESULTS: Plasmodium falciparum prevalence determined by qPCR decreased from 42% in 2006 to 9% in 2014. The P. vivax prevalence decreased from 42% in 2006 to 13% in 2010 but then increased to 20% in 2014. Parasite densities decreased 5-fold from 2006 to 2010; 72% of P. falciparum and 87% of P. vivax infections were submicroscopic in 2014. Gametocyte density and positivity correlated closely with parasitemia, and population gametocyte prevalence decreased 3-fold for P. falciparum and 29% for P. vivax from 2010 to 2014. CONCLUSIONS: Sustained control has resulted in reduced malaria transmission potential, but an increasing proportion of gametocyte carriers are asymptomatic and submicroscopic and represent a challenge to malaria control.